Experimental study on substratum preferences of early juvenile shanny, Lipophrys pholis (Pisces: Blenniidae) - Almada, Vítor Carvalho (2012)
Substratum choice tests conducted on early juveniles of Lipophrys pholis show that they clearly prefer rocky to sandy substrata. The cues involved are still unknown. It is likely that this early preference for the habitat of the adults affords them a greater protection from both predators and wave action. At this early stage agonistic behaviour, although in simple forms, is already present and may play a role in competition for the best shelters